2018
DOI: 10.3892/mmr.2018.9699
|View full text |Cite
|
Sign up to set email alerts
|

A SIRT1 agonist reduces cognitive decline in type 2 diabetic rats through antioxidative and anti‑inflammatory mechanisms

Abstract: Sirtuin 1 (SIRT1) is an NAD+-dependent protein deacetylase that is involved in cell differentiation, aging, apoptosis, physiological rhythms, metabolic regulation, oxidative stress and numerous other important biological processes. In the present study, the ability of a sirtuin-1 (SIRT1) agonist, SRT1720, to reduce cognitive decline in type 2 diabetes mellitus (T2DM) was investigated. Streptozotocin-induced male Sprague-Dawley rats were used to establish a T2DM model and the protective effect of SRT1720 and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…As NFkB modulates ROS levels and the expression of proinflammatory factors (interleukin (IL)-1, intercellular adhesion molecule 1, tumor necrosis factor α (TNF α), therefore, it can be considered to initiate the inflammatory cascade ( Wang et al, 2019 ). Previous studies also revealed that HDACi inhibits NFkB transcription, thus repressing inflammatory response ( Lu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…As NFkB modulates ROS levels and the expression of proinflammatory factors (interleukin (IL)-1, intercellular adhesion molecule 1, tumor necrosis factor α (TNF α), therefore, it can be considered to initiate the inflammatory cascade ( Wang et al, 2019 ). Previous studies also revealed that HDACi inhibits NFkB transcription, thus repressing inflammatory response ( Lu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nr4a1 activated sestrin 2, which in turn activated the AMPK pathway to induce glucose metabolism genes and glucose uptake in C2C12 cells [36]. In addition, SIRT1 agonist SRT1720 treatment can reduce FBG, inflammation, and oxidative stress in T2DM rats by inhibiting NF-kB and upregulating AMPK [22]. The insulin sensitivity and glucose homeostasis of adipose tissue were improved after SIRT1 activation, suggesting that SIRT1 activation is a promising new treatment for T2DM [37].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation often occurs during the development of chronic DM. SIRT1 can reduce the levels of FBG, oxidative stress, and inflammatory injury-related proteins in T2DM rats through the antioxidant and anti-inflammatory effects of NF-kB and AMPK-dependent mechanisms [22]. In light of this, we overexpressed Nr4a1 and LKB1 in T2DM rats, and observed the changes in the AMPK/SIRT1/NF-kB axis.…”
Section: Interaction Between Nr4a1 and Lkb1 Activates Ampk/ Sirt1 Sigmentioning
confidence: 95%
“…It has been reported that SIRT1 deacetylates p65 at lysine residue 310 and inhibits the transcriptional activation of NF‐kB, thereby inhibiting the expression of inflammatory cytokines (Xie et al, ; Wang et al, ; Nishida et al, ). SIRT1 links neurodegenerative disease, psychological stress, and depression, and it has been proposed as a novel strategy for treating depression (Alageel et al, ).…”
Section: Discussionmentioning
confidence: 99%